A Shoot Fe Signaling Pathway Requiring the OPT3 Transporter Controls GSNO Reductase and Ethylene in Arabidopsis thaliana Roots - García, María J.; Corpas, Francisco J.; Lucena, Carlos; Alcántara, Esteban; Pérez-Vicente, Rafael; Zamarreño, Ángel M.; Bacaicoa, Eva; García-Mina, José M.; Bauer, Petra; Romera, Francisco J. (Frontiers in Plant Science, 2018)
Ethylene, nitric oxide (NO) and glutathione (GSH) increase in Fe-deficient roots of Strategy I species where they participate in the up-regulation of Fe acquisition genes. However, S-nitrosoglutathione (GSNO), derived from NO and GSH, decreases in Fe-deficient roots. GSNO content is regulated by the GSNO-degrading enzyme S-nitrosoglutathione reductase (GSNOR). On the other hand, there are several results showing that the regulation of Fe acquisition genes does not solely depend on hormones and signalling molecules (such as ethylene or NO), which would act as activators, but also on the internal Fe content of plants, which would act as a repressor. Moreover, different results suggest that total Fe in roots is not the repressor of Fe acquisition genes, but rather the repressor is a Fe signal that moves from shoots to roots through the phloem (hereafter named LODIS: LOng Distance Iron Signal). To look further in the possible interactions between LODIS, ethylene and GSNOR, we compared Arabidopsis WT Columbia and LODIS-deficient mutant opt3-2 plants subjected to different Fe treatments that alter LODIS content. The opt3-2 mutant is impaired in the loading of shoot Fe into the phloem and presents constitutive expression of Fe acquisition genes. In roots of both Columbia and opt3-2 plants we determined 1-aminocyclopropane-1-carboxylic acid (ACC, ethylene precursor), expression of ethylene synthesis and signalling genes, and GSNOR expression and activity. The results obtained showed that both ‘ethylene’ (ACC and the expression of ethylene synthesis and signalling genes) and ‘GSNOR’ (expression and activity) increased in Fe-deficient WT Columbia roots. Additionally, Fe-sufficient opt3-2 roots had higher ‘ethylene’ and ‘GSNOR’ than Fe-sufficient WT Columbia roots. The increase of both ‘ethylene’ and ‘GSNOR’ was not related to the total root Fe content but to the absence of a Fe shoot signal (LODIS), and was associated with the up-regulation of Fe acquisition genes. The possible relationship between GSNOR(GSNO) and ethylene is discussed.